Nurses' In-service Education Program Content for Psychiatric Nurses: An Integrative Review - Osaka, Kyoko; Betriana, Feni; Blaquera, Allan Paulo; Soriano, Krishan; Kataoka, Mutsuko; Tanioka, Tetsuya (MALATA SAINS INDONESIA, 2024)
Introduction: The use of technologies to improve the quality of care in psychiatric nursing remains unclear. Objectives: This integrative review aims to clarify the contents of an in-service education program for psychiatric nurses. Method: The review was conducted between September 2023 and March 2024 using PubMed, ScienceDirect, ProQuest, and CINAHL databases. Result: The search returned 4993 studies, of which 50 were included in the final analysis. The results were integrated into six categories: 1) theory-based in-service educational programs; 2) nursing care using technology in various nursing situations; 3) nursing to promote the recognition of persons as participants in their care rather than as objects of care; 4) measures that ensure patient safety, such as prevention of falls and medication errors; 5) psychiatric nurses’ roles and responsibilities in addressing ethical and legal issues in the care of patients with mental illness; and 6) technological competence and caring in psychiatric nursing. Conclusion: Integrating technology into psychiatric nursing improves efficiency and safety while prioritizing ethical practices, empathy, training, equitable access, and patient dignity.